Analysis of contact conditions and its influence on strain rate and temperature in friction stir welding. (1st February 2021) - Andrade, D.G.; Leitão, C.; Dialami, N.; Chiumenti, M.; Rodrigues, D.M.
Highlights: Evolution of the contact conditions with welding parameters. Analysis of strain rate sensitivity to process parameters. Prediction of grain size evolution with process parameters. Influence of contact conditions on heat generation. Analysis of the mechanisms governing material flow. Abstract: In friction stir welding (FSW), the real contact conditions between the tool and the workpiece and the range of strain rates experienced remain quite unclear. In this work, a coupled 3D thermo-mechanical numerical model was used to simulate the FSW process. A Parametric finite element analysis of the evolution of the contact conditions, strain rates and temperatures with the processing parameters, tool dimensions and base material plastic properties was conducted. The numerical model was able to capture the evolution of the mixed slipping/sticking contact conditions with the welding time and welding parameters. The temperature and strain rate gradients obtained in the numerical simulations were validated with experimental data, by calculating the grain size distribution, in the stirred volume, using the Zener-Hollomon parameter. Full sticking, full slipping and mixed slipping-sticking contact domains were identified in a process parameters chart. It was found that, meanwhile the temperature and the sticking fraction evolve in the same way with the processing parameters, the strain rate is mainly determined by the tool rotation speed, varying from an average of 68 to 324 s −1, when the tool rotation speed is increased from 300 to 1200 rpm. The contact conditions and the base material plastic properties were also found to mutually influence the material flow. In full sticking contact, high strength materials, with high strain rate sensitivity, may display a similar flow pattern to that of low strength materials. However, coarser and more uniform grain structures may result from the welding of high strength materials, as a result of the narrower range of strain rates experienced during welding combined with high heat input. Graphical abstract: Image, graphical abstract